Left ventricular contractile reserve, coronary flow reserve, and heart rate reserve during dipyridamole stress echocardiography predict survival in non-ischemic heart failure. (14th October 2021) - Daros, C; Ciampi, Q; Cortigiani, L; Gaibazzi, N; Rigo, F; Villari, B; Antonini-Canterin, F; Lorenzoni, V; De Nes, M; Carpeggiani, C; Picano, E; ,
Abstract: Background: Left ventricular contractile reserve (LVCR), coronary flow velocity reserve (CFVR), and heart rate reserve (HRR) have recognized independent impact on outcome in heart failure (HF). They all can be simultaneously measured during dipyridamole stress echocardiography (DSE). Aim: To assess the value of comprehensive DSE in patients with non-ischemic heart failure. Methods: We evaluated 613 patients with HF, no history of coronary artery disease and no inducible regional wall motion abnormalities: 270 patients with preserved (≥50%) ejection fraction; 147 with mid-range (40–49%) ejection fraction; 196 with HF and reduced (<40%) ejection fraction. All underwent DSE (0.84 mg/kg in 6') in 5 accredited laboratories. We measured LVCR (abnormal value ≤1.1), CFVR in left anterior descending artery (abnormal value ≤2.0), and HRR (peak/rest heart rate, abnormal value ≤1.22). All patients were followed-up. Results: Abnormal CFVR, LVCR and HRR occurred in 29%, 44% and 46% of patients, respectively. After a median follow-up time of 20 months (interquartile range 12–32 months), 41 patients died. Annual mortality rate was lowest in patients (n=200) with normal response, and >10-fold higher in patients (n=96) with 3 abnormal criteria: see figure. At multivariable analysis, a reduced HRR (Hazard Ratio = 3.402, 95% Confidence Intervals 1.530–7.565, p=0.003) was the strongest SE independent predictor of all-cause death. Conclusion: Abnormal LVCR, CFVR and HRR can be frequently observed during vasodilator SE in HF patients. They target different pathophysiological vulnerabilities (myocardial function, coronary microcirculation and cardiac autonomic system) and are useful for outcome prediction. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Consiglio nazionale delle ricerche - Institute of Clinical Physiology